Safety of Early Carotid Artery Stenting for Symptomatic Stenosis in Daily Practice. (December 2018) - Alcalde-López, Jesús; Zapata-Arriaza, Elena; Cayuela, Aurelio; Moniche, Francisco; Escudero-Martínez, Irene; Ortega-Quintanilla, Joaquín; de Torres-Chacón, Reyes; Montaner, Joan; Mayol, Antonio; González, Alejandro
Abstract : Objective/Background: In 2006, the American Heart Association recommended that for preference carotid endarterectomy (CEA) or, alternatively, carotid angioplasty and stenting (CAS) for symptomatic carotid artery stenosis should ideally occur within 14 days of an ischaemic event. The aim was to determine the safety of CAS according to those recommendations in daily practice. Methods: A retrospective analysis was performed of all consecutive patients (2000–16), with ipsilateral carotid symptoms who underwent CAS for extracranial carotid stenosis ≥70%, who were previously included in a prospective database. Thirty day morbidity was assessed (any stroke without transient ischaemic attack [TIA]/amaurosis fugax), along with mortality of the procedure in the early (≤14 days after stroke onset) and delayed phases (15–180 days after stroke onset). Patients who received CAS and/or mechanical thrombectomy for acute ischaemic stroke treatment were not included. Results: In total, 1227 patients with symptomatic carotid stenosis who underwent CAS were identified. Early and delayed CAS was performed in 291 and 936 patients, respectively. Morbidity (any stroke) and mortality was 2.2% ( n  = 27) in the whole cohort ( n  = 8 [2.7%] in early vs. n  = 19 [2%] in delayed CAS; p  = .47). There were no differences in morbidity between early and delayed CAS regarding TIA ( n  = 15 vs. 36 [5.2% vs. 3.9%]; p  = .33), minor stroke ( n  = 4 vs. 5 [1.4% vs. 0.5%]; p  = .14), or major stroke ( n  = 2 vs. 6 [0.7% vs. 0.6%]; p  = .59). Two patients (0.7%) died after early CAS and eight (0.9%) after delayed CAS ( p  = .56). Conclusion: CAS may be safely performed in the early phase after an ischaemic stroke with low clinical complication rates. Further studies are needed to validate CAS safety conducted even earlier in the acute phase of ischaemic stroke.